Association Between Low Handgrip Strength and 90-Day Mortality Among Older Chinese Inpatients: A National Multicenter Prospective Cohort Study - Zhang, Xiao-Ming; Jiao, Jing; Zhu, Chen; Guo, Na; Liu, Ying; Lv, Dongmei; Wang, Hui; Jin, Jingfen; Wen, Xianxiu; Zhao, Shengxiu; Wu, Xinjuan; Xu, Tao (Frontiers in Nutrition, 2021)
Abstract Background: The knowledge of the association between low handgrip strength and mortality among older Chinese inpatients is limited. Given China's aging society, a great number of older adults require hospital admission. Objective: To explore the association between low handgrip strength and 90-day mortality, providing evidence for clinicians to predict the risk of mortality and improve clinical outcomes for older inpatients. Material and Methods: We conducted a national multicenter cohort study with a baseline survey from October 2018 to February 2019 and followed up for 90 days to record mortality outcomes. The assessment of handgrip strength was conducted using a hand dynamometer with the cutoff (handgrip strength < 28 kg for men and <18 kg for women) to define low handgrip strength. Multivariable logistic regression analysis was applied to explore the association between low handgrip strength and 90-day mortality. Results: A total of 8,910 older Chinese inpatients (mean [SD] age, 72.39 [5.68] years; 3,750 women [42.09%]), with a prevalence of low handgrip strength, at 49.57%, were included. Compared to inpatients with normal handgrip strength, inpatients with low handgrip strength were older, had less education, more were female, had lower activities of daily living (ADL) score, had lower BMI, higher frailty, higher rates of depression, and poorer cognitive function (all p<0.05). At 90 days, after adjusting for gender, age, education, frailty, depression, ADL score, malnutrition, and diagnosis, low handgrip strength was independently associated with 90-day mortality, compared to normal handgrip strength (OR=1.64,95%CI:1.14-2.37; P=0.008). Additionally, subgroup and interaction analysis showed a significant interaction effect (P=0.031) between two age groups (65-74 years older versus >=75 years old), with the OR being 3.19 (95%CI:2.07-4.93) and 1.49 (95%CI:0.87-2.55), respectively. Conclusion: Older Chinese inpatients with low handgrip strength had a 1.64-fold risk of 90-day mortality, compared to those with normal handgrip strength, indicating that clinicians need to screen early for handgrip strength and recommend corresponding interventions, such as resistance training and nutrition, as a priority for older inpatients.